Gulf Economic Update, Fall 2021 : Seizing the Opportunity for a Sustainable Recovery - World Bank (World Bank, Washington, DC, 2021)
The economic outlook for the Gulf Cooperation Council (GCC) economies appears far rosier now than it did even six months ago. Increased investment and consumption both public and private are contributing to growth while inflation remains subdued in most economies except for Saudi Arabia where it is currently at 5.5 percent and expected to fall sharply as the impact of last year’s Value-Added Tax (VAT) hike falls away. Despite this rosy picture, the authorities should continue to follow the path of prudent macroeconomic management consolidating their fiscal balances, moving ahead with the introduction of VAT in Qatar and Kuwait and focusing on reducing the role of the state in economic management. UAE’s government related entities especially those in the construction sector deserve a careful review to ensure that their borrowing remains sustainable and to adjust to the new conditions.